2020
DOI: 10.21203/rs.3.rs-36633/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical Efficacy of First and Second Series of Peptide Receptor Radionuclide Therapy in Patients With Neuroendocrine Neoplasm: A Cohort Study

Abstract: Abstract Background Peptide receptor radionuclide therapy (PRRT) is an established treatment for metastatic neuroendocrine neoplasms (NEN) with positive effects on progression free (PFS) and overall survival (OS), but only limited data exists for the effect of multiple series of PRRT. The aim of this study was to investigate PFS and OS in NEN patients treated with multiple series of PRRT conforming to the ENETS treatment protocol. Methods We included all patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…Previous cohort studies on GEP-NETs including >2000 patients demonstrated similar results including improvements in QoL, symptom control and hormone secretion in the majority of patients [32]. Patients with progression after previous response to PRRT may be retreated [33]. PRRT is effective not only in G1 and G2 tumours, but also in G3 tumours [34,35].…”
Section: Peptide Receptor Radionuclide Therapy (Prrt)mentioning
confidence: 68%
“…Previous cohort studies on GEP-NETs including >2000 patients demonstrated similar results including improvements in QoL, symptom control and hormone secretion in the majority of patients [32]. Patients with progression after previous response to PRRT may be retreated [33]. PRRT is effective not only in G1 and G2 tumours, but also in G3 tumours [34,35].…”
Section: Peptide Receptor Radionuclide Therapy (Prrt)mentioning
confidence: 68%